ln(x+1)+ln(x+1)=1

Simple and best practice solution for ln(x+1)+ln(x+1)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+1)+ln(x+1)=1 equation:


Simplifying
ln(x + 1) + ln(x + 1) = 1

Reorder the terms:
ln(1 + x) + ln(x + 1) = 1
(1 * ln + x * ln) + ln(x + 1) = 1
(1ln + lnx) + ln(x + 1) = 1

Reorder the terms:
1ln + lnx + ln(1 + x) = 1
1ln + lnx + (1 * ln + x * ln) = 1
1ln + lnx + (1ln + lnx) = 1

Reorder the terms:
1ln + 1ln + lnx + lnx = 1

Combine like terms: 1ln + 1ln = 2ln
2ln + lnx + lnx = 1

Combine like terms: lnx + lnx = 2lnx
2ln + 2lnx = 1

Solving
2ln + 2lnx = 1

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-1 + 2ln + 2lnx = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 2ln + 2lnx = 0

The solution to this equation could not be determined.

See similar equations:

| n/4+11=31 | | (v/6)+17=-1 | | 57=-25x+180-16 | | 8^4/8^6 | | 14x^3+22x^2-7x/7x | | -2+3(5x-23)=760 | | -13n+4=40 | | 142+10v=48+22v | | 30/(p+2)=2p+5 | | -9n-16=92 | | 45x^2-80=0 | | 3l-6=2(4l-9) | | -2(x+3)+5x=-2 | | -7n^2=189 | | 3x-1=8x+9/x+3 | | p^2-9=-13 | | -167=-6x-5(31+4) | | -5(3x-2)=-20 | | 3+(z/3)=6 | | (8+6x)+(-4+9c)=0 | | -12x^2-4x-5=0 | | Z-1.8=5 | | 1/2t=15 | | 4x+6(-x-26)=-172 | | a^2=-14 | | 33.5+3x+33.5-21=180 | | c-15=-34 | | X/5+6=-14 | | k^2=-78 | | -2x^2+4x-96=0 | | 33.5+3x+2x-21=180 | | 7(11)=77 |

Equations solver categories